MENDALAMI DASAR-DASAR PRAKTIK KONSELING - Sastranegara, Herlangsakati; Putri, Sophia; Asmaul, Anik; Salsabiela, Najwa; All Habsy, Bakhrudin (EPIK: Edukasi Penerapan Ilmu Konseling, 2025)
The fundamentals of counseling practice constitute an essential foundation in understanding and applying effective counseling principles. This article presents a comprehensive overview of the basic concepts of counseling, the role of counselors, commonly used techniques, and the importance of ethics in counseling practice. The discussion begins with the definition of counselling and its historical context, which helps form a strong understanding of the meaning and evolution of counseling as a discipline. Furthermore, the article discusses the role of counselors in guiding clients, facilitating personal growth, and providing emotional support. Counseling techniques covered include cognitive, behavioral, humanistic approaches, as well as family therapy and solution-focused approaches. The article also highlights the importance of adhering to ethical principles in every aspect of counseling practice, including confidentiality, professional integrity, and fairness. With a deep understanding of the fundamentals of counseling practice, readers are expected to develop the skills and knowledge necessary to guide and support individuals in overcoming challenges and achieving psychological well-being.